Tumor immunotherapy based on tumor-derived heat shock proteins (Review) - ZHANG, YUNFEI; ZHENG, LIANHE (Oncology letters, 2013)
Heat shock proteins (HSPs), the most important type of molecular chaperone, are expressed in all eukaryotic cells and have multiple functions, including the folding and unfolding of other proteins and peptides, the transport of proteins and peptides and the support of antigen presentation processes. Due to these important properties, the use of HSPs has been explored as a promising tumor immunotherapy strategy. It has been previously demonstrated that HSP peptide complex (HSP.PC) derived from tumors is the immunogenic entity that elicits powerful antitumor immune responses. Previous animal studies and phase III clinical trials have demonstrated the efficacy, safety and feasibility of HSP-based tumor vaccines. However, the limitations are also apparent and specific alternatives have been developed. The present review focused on the history of HSP-based immunotherapy, the mechanism of its immunogenicity and the previous efforts to promote the efficacy. The current review may be useful for antitumor studies based on the tumor-derived HSPs.